A study on occurrence and risk factors of domestic accidents in South India - B. V., Divya; T. M., Jayasree; J. W., Felix. A. (International Journal Of Community Medicine And Public Health, 2016)
Background: The aim of this study was to find out the frequency of domestic accidents and risk factors associated with the occurrence of domestic accidents in a semi-urban community of Chidambaram. The survey focused on age and sex distribution of population, their gender wise education, occupation and association of socio-demographic and household risk factors with the occurrence of domestic accidents. Methods: A cross-sectional survey was conducted on a representative population of Chidambaram town. The whole population in 300 households were included in this study which came around 1193. Data collection and statistical analysis was done using descriptive statistics, pearson chi square and odds ratio using SYSTAT Epi Info packages. Frequency of domestic accidents along with the risk factors namely age, sex, occupation, family size, family type, housing type, number of rooms, place of kitchen and bathrooms were analyzed. Results: Frequency of domestic accidents was found to be 8.6% in our study. Majority of the accidents were common in extreme age groups. Majority of domestic accidents were observed in females compared to males and they were 4.5 times more prone to accidents at home. A Significant statistical association was found among females and home makers along with number of rooms present in the houses. There was no significant association between the type of housing and occurrence of accidents. Majority of accidents were observed in families with more than 4 rooms. 95% of houses had their kitchen inside, among them 31.9% had domestic accidents and bathroom placed outside 36.7% of houses showed domestic accidents. Conclusions: Females are 4.5 times more prone to accidents at home. Out of 103 accidents 83 were in females. This study concludes that the majority of accidents occurred in homemakers.